Kuby immunology - Owen, Judith A. (New York: W. H. Freeman and Company, 2013)
Presenting current concepts in an experimental context, kuby immunology has been thoroughly updated to include a new chapter on innate immunity, a capstone chapter on immune responses in time and space, and many new focus boxes drawing attention to exciting clinical, evolutionary and experimental connections that help bring the material to life.
Appendix A-1-29p. B-1-6p. C-1-2p.; Glossary 1-20p.; Index 1-24p.
Keywords: B-Cell development; Immunology; Complement system; Immunodeficiency disorders; Innate immunity